ADAPTATION RESERVES OF ATHLETES FROM DIFFERENT COMBAT SPORTS DURING FUNCTIONAL TRAINING FOR MIXED MARTIAL ARTS COMPETITIONS - Savenko, A.; Chernozub, A.; Aloshyna, A. (Rehabilitation and Recreation, 2025)
Purpose – to study the characteristics of changes in adaptation reserves based on the initial resistance level of athletes from various combat sports during functional training for competitions, using classical Mixed Martial Arts (MMA) training models.Material and Methods. Eighty elite athletes from different combat sports participated in this study, completing an eight-week functional training program structured according to a training model developed for MMA competitions. Participants were divided into four groups of 20: kickboxers, Muay Thai boxers, Greco-Roman wrestlers, and judokas. The athletes’ adaptive and compensatory physiological responses were assessed under Test Loads 1 and 2 at both the beginning and the end of the study. Test Load 1 focused on creating exercise conditions that lowered the physiological resistance of athletes from all four groups. Test Load 2 was designed to deplete energy reserves within 20 seconds by performing powerful, signature elements from the studied combat sports. Blood biomarkers, including creatine phosphokinase (CPK), lactate dehydrogenase (LDH), cortisol, and creatinine, were used to evaluate adaptation reserves, compensatory responses, and potential adaptation failure.Results. At the beginning of the study, the initial baseline levels of CPK and LDH in the blood exceeded the upper limits of reference values only in kickboxers and judokas. Significant decreases in cortisol levels, accompanied by increases in CPK and LDH concentrations, were observed in these groups following Test Load 1. Decreased cortisol and CPK levels, accompanied by an increase in LDH above the normal range, were observed only in the judokas in response to Test Load 2. In the kickboxer and Muay Thai groups, LDH activity in the blood did not change in response to Test Load 2, indicating the activation of short-term adaptive mechanisms. In Greco-Roman wrestlers, in response to this load, the insufficient creatine phosphate reserves were compensated for by increased muscle glycogen accumulation. Baseline blood creatinine levels increased only in Greco-Roman wrestlers and judokas after eight weeks of functional preparation using the classical MMA training model. In kickboxers and Muay Thai boxers, CPK and LDH activity in the blood increased simultaneously in response to test loads 1 and 2.Conclusions. Adaptation fails when elite athletes’ baseline blood CPK and LDH levels exceed reference values in response to unconventional MMA-specific loads. These changes are accompanied by a reduction in blood cortisol levels, occurring alongside the depletion of creatine phosphate and muscle glycogen reserves, irrespective of the athletes’ combat sport discipline. The observed physiological responses to stress stimuli indicate both a low level of adaptation reserves and the development of functional overstrain in elite kickboxers and judokas. The application of the classical MMA training model during functional preparation for competition effectively promotes long-term adaptation, particularly in Greco-Roman wrestlers and judokas. For kickboxers and Muay Thai boxers, such training loads represent insufficient stress stimuli to accumulate creatine phosphate reserves in the muscles.